Comminution of logging residues with a tub grinder: Calculation of productivity and procurement cost of wood chips - Takuyuki Yoshioka (Croatian Journal of Forest Engineering, 2006)
An experiment on comminution of logging residues with a tub grinder was carried out in order to calculate the productivity and procurement cost of wood chips. At the investigated site, the tub grinder had a hammer mill crusher at the bottom of the tub, and a grapple loaderand a bucket loader worked as auxiliary machines for the grinder. As a result, the productivity of the tub grinder was 60.0 loose m3/PMH0, and the total comminuting cost was calculated as 5.637 US$/m3, indicating that the comminuting cost of a large-sized crusher waslower than that of a small-sized chipper. The percentage of the cost of loaders, that of carrying in, installing, and carrying out the machines, and that of constructing a landing was 53% of the total comminuting cost. When a truck with the capacity of 40 m3 transported wood chips three times a day, the costs of comminution and transportation were71.2 US$/t (DM1), which is almost on a par with those of European countries in which the energy utilization of logging residues is making steady progress. As a result of the discussion about the balance between the processing capacity of the tub grinder and that of othermachines, it seemed reasonable for Japanese forestry to consider the use of one tub grinder at several logging sites.